Fundamental chemistry for o level (teaching guide) - Gallagher Rose Marie (oxford karachi, 2012)
"Fundamental Chemistry for O Level (Teaching Guide)" provides comprehensive instructional strategies and resources to help educators effectively teach core chemistry concepts at the O Level.